L’Opéra-Comique, 1945-1970 : de nouveaux opéras et leurs livrets ou de l’audace exogène - Frank Langlois (Revue LISA)
Between 1945 and 1970, the beacon of opera in France, the Paris Opera House, a.k.a. Palais Garnier, had become a bastion of musical conservatism. Meanwhile, the Opéra-Comique, the “other” Paris opera house, a.k.a. Salle Favart, devoted to the production of those lyrical works of so-called “lighter fare” that Garnier neglected due to their own particular status and history, seemed to enjoy a burst of renewed creativity. Within that time frame, twenty six new works were first performed at Favart. Sixteen by French-speaking composers, among them Poulenc’s Mamelles de Tirésias and Voix humaine, respectively after Apollinaire and Cocteau, were given their first worldwide production. Of the remaining ten works by foreign composers given their first French performances, some were historically important and were finally granted a much belated hearing : Erwartung, Kát’a Kabanova, Fire Angel and Lulu. One needs to remember that these works were all performed in French. The goal of this paper is to examine their various lyrical genres and the literary sources of their libretti when the libretto was not an original one. The case of such composers-cum-librettists as Berg, Dallapiccola, Janáček, Menotti and Prokofiev and the directions taken by their libretti will also be looked into.